(untitled) (Altre Modernità, 2017)
Through an investigation grounded on the theoretical and methodological guidelines provided by women’s studies and reader response theories, this contribution aims to consider the ways in which Shakespeare’s female characters are used and reshaped in the lyrics of rock songs written in English by male singer-songwriters, between the 1960s and the 1990s. Given the amplitude of the topic and the ungraspable nature of such fields as popular culture and pop-Shakespeare, the author does not (and cannot) aim to be exhaustive, but rather addresses the issue by selecting four characters, Juliet, Ophelia, Cordelia, and Lady Macbeth, whose musical alter egos will be analysed by the close reading of a selection of songs written and sung by rock singer-songwriters chosen for their representativeness and their popularity. The analysis will try and answer the following questions: which aspects of the dramatic characters are highlighted or, on the contrary, omitted in the songs? What is the function of this musical use of Shakespeare’s work? Through their musical identity, do these female characters reinforce or undermine the socio-cultural and psychological oppression of women characteristic of a patriarchal culture? What can the role of these musical offshoots play in the study of Shakespeare’s reception?